Lingkungan Belajar Berbasis Lesson Study for Learning Community untuk Mahasiswa Calon Guru Matematika - Risnanosanti Risnanosanti; Mardiah Syofiana; Adi Asmara (Jurnal Elemen, 2021)
Learning communities have a positive impact on the development of the pedagogical competence of prospective mathematics teacher students. However, the nature of competition between students is more dominant in universities. This study aims to develop a valid and practical lesson study for learning community-based learning environments to improve the pedagogical competence of student mathematics teacher candidates. This study used the Rowntree model development research design and Tessmer's formative evaluation model, including self-evaluation, expert review, one-to-one evaluation, and small group evaluation. Data collection techniques used walkthrough, observation, documentation, questionnaires, interviews, and tests. The results showed that the learning environment based on the lesson study for the learning community that was developed had met valid and practical criteria and had a potential effect in improving the pedagogical abilities of student mathematics teacher candidates. Based on data analysis, the pedagogical competence of most of the students was good, with details: 94.16% of students had the competence to prepare a good lesson plan. The competence to carry out learning activities well has been mastered by 91.66% of students. Meanwhile, the understanding of the lesson study for the learning community has reached 82.5%. These results indicate that the learning community among fellow students as a lesson study for learning a community-based learning environment can improve the pedagogical competence of student mathematics teacher candidates.